2013
DOI: 10.1021/jp312263j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nanometric-Sized Phosphate Clusters in Bioactive Glasses As Revealed by Solid-State 31P NMR

Abstract: Bioactive glasses are able to form strong bonds to bone. This property, crucial for medical applications, depends on the glass composition and structure. Dissolution of phosphates in melt-quenched silicate glasses raises the question of chemical homogeneity and possible formation of clusters. A detailed structural characterization of the bioactive glasses is thus highly desirable. In this work, the nature of the distribution of phosphate units in a melt-quenched bioactive glass is elucidated for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
74
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 31 publications
11
74
1
3
Order By: Relevance
“…The extent of clustering also depends on the silicate content. MD simulations (45) have shown that for compositions based on Bioglass 45S5 with constant phosphate content the amount of phosphate clusters, typically containing four or five phosphate groups, a number consistent with NMR data from a comparable, sodium--free composition (38) , increases with increasing silicate content. By contrast, such clusters were negligible for compositions with silicate network connectivity lower than 2.9 (41,46) .…”
Section: Techniquesmentioning
confidence: 55%
See 4 more Smart Citations
“…The extent of clustering also depends on the silicate content. MD simulations (45) have shown that for compositions based on Bioglass 45S5 with constant phosphate content the amount of phosphate clusters, typically containing four or five phosphate groups, a number consistent with NMR data from a comparable, sodium--free composition (38) , increases with increasing silicate content. By contrast, such clusters were negligible for compositions with silicate network connectivity lower than 2.9 (41,46) .…”
Section: Techniquesmentioning
confidence: 55%
“…Data on P--P separation from combined MD simulation/solid--state NMR experiments later confirmed the finding that larger agglomerations of phosphate, containing three or more phosphate groups, only occurred in glasses with phosphate contents above 4 mol% (46) . By contrast, recent 31 P spin--counting solid--state NMR experiments showed nanometre--sized phosphate clusters consisting of five to six orthophosphate groups in a sodium--free version of Bioglass 45S5 (Figure 3 (38) ). These results suggest that the occurrence of clustering is dependent on the phosphate content of the glass, with phosphate clusters being more likely to be present in high phosphate content compositions.…”
Section: Techniquesmentioning
confidence: 76%
See 3 more Smart Citations